The role of the elite groups in the process of transformation of protest potential in the mass mobilization in Ukraine - Воробйова, Т. Л. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
Protest is an actual problem of political process as Ukrainian political events of 2013-2014 demonstrated. So this problem should be explored in order to regulate and prevent its adverse effects. The structure and some factors that determine the transition from psychological marks of the protest potential to the action were presented. The elite’s role in this process and its influence on citizens' moods were defined, so the dynamics of its formation during the period of Ukraine's independence were traced. Some stages that reveal the shape of formation of the political and economic elite, the goals and the ways of their interaction, the way in which the external factors that stimulate or, conversely, block the protest potential, are divided.